Antioxidants and Nanotechnology: Promises and Limits of Potentially Disruptive Approaches in the Treatment of Central Nervous System Diseases. Issue 3 (18th December 2019) - Martinelli, Chiara; Pucci, Carlotta; Battaglini, Matteo; Marino, Attilio; Ciofani, Gianni
Abstract: Many central nervous system (CNS) diseases are still incurable and only symptomatic treatments are available. Oxidative stress is suggested to be a common hallmark, being able to cause and exacerbate the neuronal cell dysfunctions at the basis of these pathologies, such as mitochondrial impairments, accumulation of misfolded proteins, cell membrane damages, and apoptosis induction. Several antioxidant compounds are tested as potential countermeasures for CNS disorders, but their efficacy is often hindered by the loss of antioxidant properties due to enzymatic degradation, low bioavailability, poor water solubility, and insufficient blood–brain barrier crossing efficiency. To overcome the limitations of antioxidant molecules, exploitation of nanostructures, either for their delivery or with inherent antioxidant properties, is proposed. In this review, after a brief discussion concerning the role of the blood–brain barrier in the CNS and the involvement of oxidative stress in some neurodegenerative diseases, the most interesting research concerning the use of nano‐antioxidants is introduced and discussed, focusing on the synthesis procedures, functionalization strategies, in vitro and in vivo tests, and on recent clinical trials. Abstract : Nanotechnological approaches for antioxidant therapy of central nervous system diseases improve the bioavailability and the delivery of antioxidant molecules, prevent their degradation, and facilitate blood–brain barrier crossing and targeting to the desired sites within the brain.